Effects of fibre, starch and fat intake on gastrointestinal transit time, digestibility, and microbial fermentation products in red-footed tortoise (Chelonoidis carbonaria) - Di Santo, Ludmilla G. [UNESP]; Braos, Lucas B.; Vitta-Takahashi, Amanda [UNESP]; Borges, Monique Harumi S. [UNESP]; Pacheco, Letícia G. [UNESP]; de Paula Cerdan, Isaura [UNESP]; Carciofi, Aulus C. [UNESP] (Taylor & Francis, 2025)
The comprehension of the digestive strategy of red-footed tortoises (Chelonoidis carbonaria) is necessary for effective dietary practices, which prevent metabolic disorders often seen in captivity. The present study evaluated the effects of three extruded diets (high in fibre [Control], high in starch [Starch], and high in fat [Fat]) on the tortoises' preference, nutrient digestibility, faeces quality, fermentation products, and gastrointestinal transit time (GTT). Eighteen adult red-footed tortoises (9 males and 9 females) were used to compare diet palatability. Tortoises were randomly divided into three groups of six, balanced for sex and assigned to one of the experimental diets. The total tract apparent digestibilities (TTAD) of nutrients and energy was measured using chromium oxide (0.25%) as a marker, while GTT was assessed with ferric oxide (2.5%). Faeces were collected for analysis of short and branched-chain fatty acids, lactate, ammonia, and pH. Data were analysed using analysis of variance (ANOVA), and means were compared using Tukey's test (p < 0.05). Diet preference was evaluated with paired t-test, and first-choice preferences by the Chi-square test (p < 0.05). The tortoises showed preference for the Starch and Fat diets, consuming less of the Control diet, high in fibre (p < 0.05). The TTAD of dry matter, organic matter, and gross energy was highest for the Starch diet, intermediate for the Fat diet, and lowest for the Control diet (p < 0.05). The TTAD of fat was lowest for the Fat diet, which resulted in faeces with a high fat content (33.9 ± 2.64% faecal DM; p < 0.05). Tortoises fed the Control diet showed a trend towards a longer GTT, nearly three days longer than those on the other diets (p = 0.075). Short- and branched-chain fatty acids, and faecal lactate, were similar across diets (p > 0.05), though ammonia concentration was lower in the Control diet compared to the Starch diet (p < 0.05). In conclusion, red-footed tortoises showed a preference for diets high in starch and fat over the high fibre formulation. Fat TTAD was limited, decreasing with higher fat intake. Faecal concentrations of fermentation products remained consistent across diets, suggesting extensive absorption of these compounds due to the tortoises' long GTT and the reverse peristalsis.